P-271 Is proactive primary end of life care possible and sustainable?. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Thomas, Keri; Clifford, Collette; Wilson, Julie Armstrong
Abstract : Aim: Crises are frightening especially near the end of life. Primary care teams are pivotal in caring for patients in the final years of life, enabling more to live well and die where they choose, and reduce inappropriate crises and hospitalisation. With increasing pressures from the ageing population, rising mortality and limited resources, a more proactive approach to meeting these challenges is required. The Gold Standards Framework (GSF) Quality Improvement Programme has been influential in EOLC since 2000 with most UK general practitioners using GSF foundation principles. We report on the findings of the first 17 GP practices undertaking GSF Going for Gold training and accreditation with some reaccredited three years later, demonstrating what is possible to achieve. Method: Primary care teams undertake a practice-based distance-learning GSF Gold programme with optional interactive workshops over 6–12 months. Evaluations before and after in preparation for accreditation include key outcome ratios, on-line After Death Analysis plus submission of a portfolio of evidence and assessment interview. Results: Cumulated findings for the accredited practices show significant improvements, including some reaccredited three years later demonstrating long-term sustainability. Practices demonstrate enhanced proactive end-of-life care, with earlier identification of over 60% of their patients who died, offering ACP discussions to over 65%, leading to more home deaths and improved outcomes for patients and carers. Conclusion: Improving care for people in their last year of life in GP Practices with proactive person-centred care is pivotal to meeting the challenges of the ageing population, and making best use of limited resources. The GSF Gold programme reported here, is an example of a practical, well-received evidence–based quality improvement, leading to more proactive planned care in line with peoples' preferences, meeting the increasing needs of the ageing population.